Students' Learning Interest Analysis of Mathematics Learning in the New Normal Era - Damanik, Riska Herdiyanti; Herman, Tatang (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2022)
This research is a type of descriptive qualitative research. The purpose of this study was to analyze and describe the learning interests of third grade students at Al Azhari Global School Cikampek for the 2021/2022 academic year in Karawang district. The results of this study indicate that the average percentage of students' overall interest in learning mathematics is 78.75%. So it can be concluded that most students have an interest in learning mathematics. The questionnaire instrument in this study consisted of four indicators consisting of feelings of pleasure, attention, interest and involvement of students in learning mathematics. Each indicator in the instrument consists of 4-8 items in the category of positive and negative statements in accordance with predetermined indicators. The indicator that obtained the greatest results was the student's interest with the results of 87.98%. In the second order there is an indicator of feeling happy with the results of 82.55%. Furthermore, in the third order shows the acquisition of a score of 75.87 with an indicator of attention to mathematics learning. The lowest gain shows a result of 68.60% on the indicator of student involvement. The results of this study can be used as an illustration of the interest that students have in learning mathematics. Especially in the post-pandemic transition situation, namely in the learning of the new normal era.